2018
DOI: 10.1016/j.heliyon.2018.e00787
|View full text |Cite
|
Sign up to set email alerts
|

Optimized dispersion quality of aqueous carbon nanotube colloids as a function of sonochemical yield and surfactant/CNT ratio

Abstract: In this paper, we propose and verify a theoretical model of the development of dispersion quality of aqueous carbon nanotube (CNT) colloid as a function of sonochemical yield of the sonication process. Four different surfactants; Triton X-100, Pluronic F-127, CTAB and SDS were studied. From these four SDS had the lowest dispersion performance which was surprising. Optical dispersion quality results fits well with proposed theoretical model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…It has been stated that, for dispersing CNTs it is preferable for the surfactant to have a relatively high HLB (hydrophilic-lipophilic balance) value [ 29 ]. This assumption was proven false in our previous study [ 37 ]. Not only are the surfactant’s nature and energy carried into the dispersed system, but the concentration of the surfactant also has a crucial role in the dispersion process [ 38 ].…”
Section: Introductionmentioning
confidence: 88%
“…It has been stated that, for dispersing CNTs it is preferable for the surfactant to have a relatively high HLB (hydrophilic-lipophilic balance) value [ 29 ]. This assumption was proven false in our previous study [ 37 ]. Not only are the surfactant’s nature and energy carried into the dispersed system, but the concentration of the surfactant also has a crucial role in the dispersion process [ 38 ].…”
Section: Introductionmentioning
confidence: 88%
“…Figure 1 shows that the opacity at 500 nm as a function of sonication energy follows a logistic curve (dashed line) deducted in the author’s earlier work [ 18 ]. Since opacity is related to dispersion quality, one can use it to optimize the sonication energy to prevent oversonication and damaging the tubes.…”
Section: Resultsmentioning
confidence: 69%
“…The selection of used surfactant in this study was done based on the previous studies [14,15] and the requirement to reach an efficient foaming capability. Therefore, Triton X-100 was selected and it is a non-ionic surfactant that has a hydrophilic polyethylene oxide chain and an aromatic hydrophobic group in its molecular structure.…”
Section: Methodsmentioning
confidence: 99%
“…The true conductivity potential of CNTs can be uncovered when the dispersing step to a liquid medium is performed properly to form a percolation network. Recent studies have revealed that the process of dispersing CNTs in a water-based system can be optimised so that the outcome functionality increases exponentially [14,15]. It is reported in those articles that, when using sonication as a dispersing process, the applied sonication energy to the dispersion and a properly selected surfactant play a key role when optimizing conductivity properties and dispersion quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation